THE ROLE OF WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE - Sagita, Elga Salsabila; Sutianingsih, Sutianingsih (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The goal of this study is to evaluate the influence of the work environment and work discipline on employee performance and motivation. The sample that was obtained consisted of 114 workers. According to the findings of the research, the environment of the workplace has a positive and significant impact on the drive to perform one's job. Positive and significant effects on work motivation can be attributed to the presence of work discipline. The environment in which employees work has a significant and beneficial impact on the performance of those employees. The performance of employees is positively impacted by work discipline, however, this impact is not large. Motivation plays a part in mediating the relationship between worker performance work environment and discipline. Keywords: employee performance, work discipline, work environment, and work motivation.